Evaluation of the shedding routes and serological patterns in experimentally-induced Brucella melitensis in dexamethasone-treated and transport-stressed goats - Tanko, Polycarp Nwunuji; Emikpe, Benjamin Obukowho; Mohd Yusoff, Md Sabri (Veterinary World, 2013)
Aim: To identify and evaluate the shedding routes and patterns following experimentally-induced Brucella melitensis infection in dexamethasone-treated and transport-stressed goats. Materials and Methods: Twenty four healthy, adult goats were divided into 4 groups: A, B, C and D respectively. Group A was treated with dexamethasone for 8 days prior to inoculation with 107 Colony Forming Units of B. melitensis via the intraocular route. Group B was transported for 3 hours prior to inoculation with a similar dose. Group C was inoculated with a similar dose without subjecting the animals to any prior treatment, and this group served as our positive control. Group D was not inoculated with the infective dose and served as our negative control. Blood samples along with nasal, ocular, and vaginal swabs were collected on days 0, 3, 7, 10, 14, and weekly thereafter until day 63 post inoculation (pi) and were analyzed by PCR, Rose Bengal Plate Test (RBPT), and indirect ELISA techniques. Results: The nasal, ocular and vaginal swabs tested positive for Brucellosis with PCR from day 7, with nasal route being the first and most consistent route to reveal the positive results. Group B showed the earliest onset of shedding the bacterium (day 7) followed by group A which started from day 10 and shed relatively more positive of the bacterium via the routes examined. Blood samples tested positive with PCR from day 7 through 14 and the results were inconsistent subsequently. Sera samples tested positive with RBPT on day 14 in all the 3 infected groups but more consistent in group C. On the other hand, tests using ELISA showed positive results from day 7 pi, with group C having a 100% seroconvertion –while groups A and B showed only 50% seroconvertion. Conclusion: The consistent shedding via the nasal, ocular, and vaginal routes in groups A and B implied possible immunosuppression in the infected animals. We recommend that programs designed to control Brucellosis should consider analyzing a larger number of biological samples to enhance the accuracy of identification of shedders.